Blood vessel remodeling in pig ovarian follicles during the periovulatory period: an immunohistochemistry and SEM-corrosion casting study - Berardinelli Paolo; Di Giacinto Oriana; Bernabò Nicola; Rinaldi Carlo; Russo Valentina; Palmerini Maria; Martelli Alessandra; Nottola Stefania; Macchiarelli Guido; Barboni Barbara (BMC, 2009)
Abstract Background The present research aims to describe the process of vascular readjustment occurring in pig ovary during the periovulatory phase (from LH surge to ovulation) that drives the transformation of the follicle, a limited blood supplied structure, into the corpus luteum, a highly vascularised endocrine gland required to maintain high levels of progesterone in pregnancy. The swine model was chosen because it is characterized by a long periovulatory window (about 40-44 hrs-similar to human) that permits to recover follicles at a precise endocrinological timing. Methods By validated hormonal protocol (eCG+hCG), able to mimic the physiologic gonadotropin stimulation, preovulatory follicles (PreOFs, 60 h-eCG), follicles in the middle (early periovulatory follicles, EPerOFs, 18 h-hCG) or late (LPerOFs, 36 h-hCG) periovulatory phase were isolated from prepubertal gilts. To understand the angiogenic process, morphological/morphometrical analyses were performed by combining immunohistochemistry (IHC) and SEM of vascular corrosion casts (VCC) techniques. Results PreOFs showed a vascular plexus with proliferating endothelial cells (EPI). This plexus was characterized by a dense inner capillary network, with angiogenic figures, connected to the outer network by anastomotic vessels (arterioles and venules of the middle network). EPerOFs decreased their EPI, blood vessel extension in the outer network, and evidenced a reduced compactness of blood vessels. In LPerOFs, a rapid neovascularization was associated to an intensive tissue remodeling: the follicle acquired an undulated aspect presenting arterioles/venules near the basal membrane, increased vascular extension by EPI, sprouting and non-sprouting angiogenesis. The analysis of vascular geometric relations and branching angles evidenced similar values at all stages. Conclusion These data allow us to hypothesize that EPerOFs are in a quiescent status. LPerOFs represent the "metamorphic" follicles that rapidly turn-on angiogenesis to sustain a successful corpus luteum formation. Particularly, it is interesting to underlie that the non-sprouting angiogenesis, typical of structures in rapid neovascularization, occurred only in the LPerOFs. Moreover, vascular geometric relations showed as blood vessel remodeling occurs with the "maximum output and the minimum energetic expense". This knowledge will allow to better understand the mechanisms regulating the reproductive success and to clarify the complex physiological angiogenic process in adult tissues.